2018
DOI: 10.1186/s12941-018-0256-y
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of Klebsiella pneumonia encoding genes for CTX-M, TEM-1 and SHV-1 extended-spectrum beta lactamases enzymes isolated from urinary tract infection

Abstract: BackgroundThe extended- spectrum β-lactamase producing bacteria are widely spread worldwide. The productions of these enzymes cause bacterial resistance to a wide range of antibiotics. The aim of this study was to investigated the frequency of K. pneumonia encoding genes for CTX-M, TEM-1 and SHV-1 extended-spectrum beta lactamases enzymes isolated from urinary tract infection.MethodsThis study is cross-sectional study. All K. pneumonia isolates from urine samples, which had grown on media culture more than 105… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Klebsiella and Enterococcus were relatively increased in the diabetes group. Klebsiella is a common conditional pathogenic bacterium that causing respiratory and urinary tract infections when host immunity is impaired [22]. Enterococcus is a nosocomial pathogen which can cause UTI and endocarditis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella and Enterococcus were relatively increased in the diabetes group. Klebsiella is a common conditional pathogenic bacterium that causing respiratory and urinary tract infections when host immunity is impaired [22]. Enterococcus is a nosocomial pathogen which can cause UTI and endocarditis [23].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of blaSHV depends on the rate of ESBL infection caused by K.pneumoniae . A study by Dehshiri et al,38 on the occurrence of ESBL-producing K.pneumoniae in patients with urinary tract infection concluded that the prevalence of blaSHV was very high (85%), compared with that of blaCTX-M and blaTEM at 30% and 16%. In the present investigation, the prevalence of blaSHV was greater in K.pneumoniae (56.7%) than E.coli (17.7%).…”
Section: Discussionmentioning
confidence: 99%
“…In Iran, studies have shown that in Klebsiella spp., resistance to extended spectrum beta lactams is mainly mediated via the production of CTX-M variants (CTX-M-15, CTX-M-3, CTX-M-8, CTX-M-1, and CTX-M-2) (Feizabadi et al, 2010; Peerayeh et al, 2014; Bialvaei et al, 2016; Akya et al, 2018; Dehshiri et al, 2018) and to a lesser degree via SHV (SHV-12, SHV-11, SHV-5) (Feizabadi et al, 2010; Shakib et al, 2018), TEM genes (Gholipour et al, 2014; Maleki et al, 2018) and others (VEB, PER, and GES) (Sedighi et al, 2017). pAmpC beta lactamase genes were reported by two studies in clinical isolates of Klebsiella pneumoniae (Mansouri et al, 2012; Kiaei et al, 2018).…”
Section: Distribution Of Multi-drug Resistant Organisms In Humansmentioning
confidence: 99%